PSIX-19 The impact of piglet nursing location along the sow udder line on piglet gain and subsequent weaning weight. (30th November 2020) - Dierking, Shannon L; Monegue, Harold J; Lindemann, Merlin D
Abstract: Piglet weaning weight is a critical factor that influences post-weaning growth and performance. Weaning weight is a function of birth weight and the amount and nutrient density of the milk consumed during lactation. Milk production is influenced by sow mammary gland development and diet consumption but may also be a biological function of teat location along the udder line. The objective of this study was then to determine the effects of piglet nursing location along the udder on overall piglet gain and weaning weight. A total of 1, 078 individual piglets were observed during the nursing period at three time points during lactation. The teat pairs along the udder line were labeled from anterior to posterior (1-7, respectively) to define nursing location. At the end of the lactation period, the observed piglet nursing location was evaluated for both actual weaning weight and overall piglet weight gain during lactation. Data were evaluated by analysis of variance with the statistical model utilizing litter size as a covariate. As expected, when litter size was utilized as a covariate, there was a significant effect on piglet weaning weight (P < 0.0001), and there was both a linear and quadratic effect of location (L, P < 0.0001; Q, P = 0.0009) on both weaning weight and lactation piglet gain. Heavier piglets were weaned from more anterior teats (teat pairs 1-4), with the numerically heaviest piglets weaned from teat pair 4 (6.12 kg), with the lowest weight piglets being weaned from teat pair 7 (5.17 kg). Piglet weight gain during lactation was impacted by litter size (P < 0.0001), but nursing location did not affect lactation weight gain (P = 0.57). Due to the differences in piglet weights at weaning, it can be concluded that piglet nursing location influences overall piglet weaning weight.